2019
DOI: 10.2106/jbjs.18.00867
|View full text |Cite
|
Sign up to set email alerts
|

Altered Range of Motion and Plantar Pressure in Anterior and Posterior Malaligned Total Ankle Arthroplasty

Abstract: Background: Malaligned ankle arthroplasty components have been associated with increased postoperative pain and reduced ankle range of motion. With this study, we aimed to quantify how anterior and posterior malalignment of the talar component affects foot bone kinematics and plantar pressures in a dynamic, cadaveric gait simulation. Methods: Ten cadaveric foot specimens received a modified ankle prosthesis. Proper alignment was defined as the prosthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…TAA can maintain a normal range of motion of the ankle joint, prevent degeneration of adjacent joints, and help patients restore normal gait and function [ 19 , 20 ]. However, ankle replacement is not as mature as hip and knee replacement due to factors including prosthetic design and anatomical characteristics [ 21 , 22 ]. A recent meta-analysis compared ankle arthrodesis with ankle replacement using third-generation prostheses and suggested that the overall complication rate was higher in the AAA group, but the revision rate was higher in the TAA group [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…TAA can maintain a normal range of motion of the ankle joint, prevent degeneration of adjacent joints, and help patients restore normal gait and function [ 19 , 20 ]. However, ankle replacement is not as mature as hip and knee replacement due to factors including prosthetic design and anatomical characteristics [ 21 , 22 ]. A recent meta-analysis compared ankle arthrodesis with ankle replacement using third-generation prostheses and suggested that the overall complication rate was higher in the AAA group, but the revision rate was higher in the TAA group [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…1). 3D kinematic analysis of individual bones is valid and reliable only via invasive approaches such as intracortical pins (Arndt et al, 2007;Lundgren et al, 2008;Westblad et al, 2002), actuator-controlled gait simulators in vitro (McKearney et al, 2019;Nester et al, 2007;Okita et al, 2013;Saito et al, 2019), quasi-dynamic radiostereometric analysis (RSA) which involves insertion of intracortical markers (Lundberg, 1989;Lundberg et al, 1989aLundberg et al, , 1989bLundberg et al, , 1989c and bi-planar video fluoroscopy (Komistek et al, 2000;Lenz et al, 2021). Intracortical pins, actuator controlled gait simulators and RSA methods all track bones very precisely by utilizing at least three non-collinear markers inserted surgically into each bone segment of interest.…”
Section: Modeling the Foot Segmentsmentioning
confidence: 99%
“…Due to the novelty of WBCT technology, there are limited data on its usefulness in reducing postoperative complications, and further clinical studies are warranted. While correlations between implant positioning and outcomes have been reported [8,33,42], further investigation is needed to determine the position that yields optimal outcomes. The available evidence shows that using preoperative WBCT for intraoperative procedures can both decrease operative time and increase rates of implant survival [1,41].…”
Section: Use Of Wbct In Taamentioning
confidence: 99%
“…While not yet approved for use in TAA, advanced intraoperative radiologic techniques have already improved surgical methods for multiple procedure types in foot and ankle surgery [33,41]. Unlike traditional fluoroscopy, which produces 2-dimensional (2D) images, intraoperative 3D fluoroscopic imaging uses a mobile isocentric C-arm to obtain CT-like 3D images.…”
Section: Intraoperative Imagingmentioning
confidence: 99%